2008
DOI: 10.1177/0269881107087976
|View full text |Cite
|
Sign up to set email alerts
|

A new self-rating scale for detecting atypical or second-generation antipsychotic side effects

Abstract: We aimed to construct and assess a new self rating scale to detect the side effects of second generation antipsychotics. This scale was designed to allow a timely, sensitive and reliable method of gathering information on the number and severity of side effects an individual suffers from. The Glasgow Antipscyhotic Side-effect Scale (GASS) was developed after literature review, discussion with members of the mental health team and with service user feedback. Fifty indivudals taking second generation antipsychot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
136
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(137 citation statements)
references
References 11 publications
(12 reference statements)
0
136
1
Order By: Relevance
“…For instance, Waddington et al [43] found that antipsychotic polypharmacy is associated with increased mortality and reduced survival among patients with schizophrenia. In addition, newer outcome measures such as the Glasgow Antipsychotic Side-effect Scale must be taken into consideration for future assessments, which has been structured for detecting the side effects of SGAs and has shown to have good discriminatory power and construct validity, along with good test/re-test reliability [44]. Some of the limitations of this study could be summarized as follows: (1) small sample size; (2) no direct comparison between flupenthixol decanoate and aripiprazole regarding their individual therapeutic efficacy; (3) the short duration of the study; and (4) gender-based sampling.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Waddington et al [43] found that antipsychotic polypharmacy is associated with increased mortality and reduced survival among patients with schizophrenia. In addition, newer outcome measures such as the Glasgow Antipsychotic Side-effect Scale must be taken into consideration for future assessments, which has been structured for detecting the side effects of SGAs and has shown to have good discriminatory power and construct validity, along with good test/re-test reliability [44]. Some of the limitations of this study could be summarized as follows: (1) small sample size; (2) no direct comparison between flupenthixol decanoate and aripiprazole regarding their individual therapeutic efficacy; (3) the short duration of the study; and (4) gender-based sampling.…”
Section: Discussionmentioning
confidence: 99%
“…The tolerability-related burden associated with these AEs may lead to poor adherence or earlier treatment discontinuation and, as a result, worse functional outcomes [2,11,12]. Several observer-reported and self-reported AE assessment scales for antipsychotic medications are available [2,1317]. Self-reported scales include the Udvalg for Kliniske Undersøgelser (UKU) Side-Effect Rating Scale, the Liverpool University Neuroleptic Side-Effect Rating Scale (LUNSERS), and the Glasgow Antipsychotic Side-Effect Scale (GASS).…”
Section: Introductionmentioning
confidence: 99%
“…As such, the LUNSERS cannot be readily used to compare the tolerability profiles of antipsychotics and has not been included in many pivotal studies. The GASS resolves some ambiguity of phrasing in the LUNSERS [2] and enables patients to report whether an AE is ‘distressing’ in addition to rating its severity [17]; however, like the LUNSERS, the GASS contains only a subset of the AEs that can occur with antipsychotics and therefore has limited utility. Another approach to estimating AEs is to consider the subjective nature of the AE.…”
Section: Introductionmentioning
confidence: 99%
“…Patients provide their responses to these questions by circling relevant side effects. An additional open question enquires about any other possible side effects [31].…”
Section: Introductionmentioning
confidence: 99%
“…The GASS takes 5 minutes to complete (21 items for men and women) and contains self-explanatory questions in everyday plain English while providing a structured systematic method of reviewing antipsychotic side effects [31].…”
Section: Introductionmentioning
confidence: 99%